The Effect of Brain Dance on Children’s Creativity - Yetti, Elindra; Siti Syarah, Erie; Iasha, Vina (Opción, 2019)
The creative needs of the digital age have made educators focus on developing creativity early on. Early research has proven the creativity developed in early childhood. The purpose of this study is to look at the effect of Brain Dance on creativity in Early Childhood. This study uses a quasi-experimental method with one-group pretest-posttest design, with paired t-test used to analyze data and test hypotheses. 30 early childhood in this study. This study found the results of sig. 0,000, indicating that the Brain Dance Training Program, can significantly influence creativity in a positive direction. Future research can evaluate the long-term effects of the Brain Dance training program.